Mahkota Dewa (God’s Crown) Fruit Extract Inhibits the Formation of Periodontal Pathogen Biofilms in vitro - Diajeng Celia Radita; Armelia Sari Widyarman (Journal of Indonesian Dental Association, 2019)
Introduction: Mahkota dewa (Phaleria macrocarpa) is an Indonesian fruit that contains antibacterial compounds, such as flavonoids, saponins, and tannins; it has been used as an alternative treatment for controlling infection. Objectives: This study aimed to examine the effect of mahkota dewa fruit extract on the formation of Porphyromonas gingivalis (P. gingivalis), Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), and Treponema denticola (T. denticola) biofilms in vitro. Methods: God’s crown fruit was extracted using the maceration technique, and then diluted into different concentrations (25%, 12.5%, 6.25%, 3.125%, and 1.56%) using phosphate buffered saline (PBS). P. gingivalis ATCC-33277, A. actinomycetemcomitans ATCC-29522, or T. denticola ATCC-35405 were cultured in brain heart infusion (BHI) broth, 24h (anaerobic-condition), and then each type of bacteria (108CFU/mL) was distributed into a 96-well microplate to form a biofilm. Subsequently, the fruit extracts were distributed into the biofilm-containing well plates and incubated for 1h, 6h, and 24h. A biofilm without the fruit extract and chlorhexidine-gluconate (0.2%) was used as the negative and positive control, respectively. Crystal violet (0.5%w/v) was used to determine the density of the remaining biofilm using a microplate spectrophotometer (600 nm). Data were statistically analyzed using one-way ANOVA, and p <0.05 was set as the level of significance. Results: The mahkota dewa fruit extracts significantly inhibited the formation of a biofilm for all three bacterial strains at all concentrations and for each incubation time (p <0.05) based on optical density (OD)±SD. The best concentration of fruit extract to inhibit biofilm formation was 25% for P. gingivalis (OD=0.19±0.06), 12.5% for A. actinomycetemcomitans (OD=0.14 ± 0.16), and 25% for T. denticola (OD=1.17±0.19) in comparison to the biofilm mass of the negative control, which was 1.67±0.06, 1.17±0.34, 2.66±0.38 for P. gingivalis, A. actinomycetemcomitans, and T. denticola, respectively. Conclusion: Based on these results, mahkota dewa fruit extract can inhibit the formation of biofilm on P. gingivalis, A. actinomycetemcomitans, and T. denticola, and it may potentially be used to prevent the infection associated with periodontal disease.